Activity and bioaccessibility of antioxidants in yoghurt enriched with black mulberry as affected by fermentation and stage of fruit addition. (June 2021) - Durmus, Nihal; Capanoglu, Esra; Kilic-Akyilmaz, Meral
Abstract: Pasteurised whole milk was acidified with bacterial culture or glucono-δ-lactone (GDL) to determine effects of fermentation and pH reduction on activity and in vitro bioaccessibility of antioxidants and physical properties of yoghurt with black mulberry. Both pH reduction and fermentation were found to influence activity and bioaccessibility of antioxidants in mulberry yoghurt. Total phenolic content of the sample prepared with bacterial culture was higher than that of the sample with GDL, while there was a similar level of reduction in both samples after three weeks of storage at 4 °C. Fermentation with the bacterial culture yielded lower copper reducing activity but higher DPPH scavenging activity compared with acidification with GDL. Bioaccessibility of the antioxidants in in vitro gastrointestinal system was less than 25% in all samples. Addition of fruit after acidification or fermentation of milk, rather than before, resulted in higher antioxidant activity, higher consistency coefficient and less serum separation.